Penilaian Uji Konsistensi Dokumen AMDAL yang disahkan oleh Komisi Penilai AMDAL Provinsi Sumatera Selatan: The Assessment of EIA Document Consistency Aspect Validated by EIA Assessment Commission of South Sumatra Province - Rian Syafni; Dedik Budianta; Moh. Rasyid Ridho (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
Environmental Impact Assessment (EIA) is one of the instruments to prevent environmental pollution and/or damage (Undang-Undang 32, 2009). Success in preventing environmental pollution is closely related to the quality of the EIA document, especially the quality of the consistency aspects, such as the consistency between the hypothetical significant impact and the initial environmental baseline, the estimated magnitude of the impact, the environmental management and monitoring plan. Therefore, it is very necessary to assess the consistency of the EIA Document in the Province of South Sumatra. This research aims to assess the consistency test of the EIA Document approved by the EIA Assessment Commission of South Sumatra Province. This study used descriptive qualitative method. The research sample was taken using a total sampling technique, all EIA Documents that have been assessed by the EIA Assessment Commission of South Sumatra Province between 2018-2020 and already have an Environmental Feasibility Decree totaling 12 (twelve) documents are used as research samples. The results showed that 5 (five) documents (42%) had very good consistency,               6 (six) documents (50%) had good consistency and 1 (one) document (8%) ) had a bad consistency.